In Vitro α-glucosidase Inhibition and Computational Studies of Kaempferol Derivatives from Dryopteris cycanida - Amin, Surriya; Ullah, Barkat; Ali, Mumtaz; Khan, Haroon; Rauf, Abdur; Khan, Sher A.; Sobarzo-Sánchez, Eduardo (Current Topics in Medicinal Chemistry, 2020)
Background: Dryopteris cycadina has diverse traditional uses in the treatment of various human disorders which are supported by pharmacological studies. Similarly, the phytochemical studies of this plant led to the isolation of numerous compounds. Methodology: The present study deals with α-glucosidase inhibition of various kaempferol derivates including kaempferol-3, 4/-di-O-α- L-rhamnopyranoside 1, kaempferol-3, 5-di-O-α-L-rhamnoside 2 and kaempferol-3,7-di-O-α- L-rhamnopyranoside 3. Results: The results showed marked concentration-dependent inhibition of the enzyme when assayed at different concentrations and the IC50 values of compounds 1-3 were 137±9.01, 110±7.33, and 136±1.10 mM, respectively far better than standard compound, acarbose 290±0.54 mM. The computational studies revealed strong docking scores of these compounds and augmented the in vitro assay. Conclusion: In conclusion, the isolated kaempferol derivatives 1-3 from D. cycadina exhibited potent α- glucosidase inhibition.
Keywords: Dryopteris cycadina